The effect of the SIMS Programme versus existing preschool oral healthcare programme on oral hygiene level of preschool children: study protocol for a cluster randomised controlled trial - Zamros Yuzadi Mohd Yusof; Nurul Hayati Anwar; Nor Azlida Mohd Nor; Mariani Md Nor; Siti Ezaleila Mustafa (Trials, 2021)
Abstract Background Despite the implementation of the preschool oral healthcare programme (POHP) for 5–6-year-old children over the past 3 decades in Malaysia, dental plaque and caries levels in this age group remain high. Among the child-level attributable factors are unhealthy self-care behaviours (poor oral hygiene and high sugary diet). In order to improve the children’s oral health, an improved programme called the ‘Senyuman Indah Milik Semua’ Programme (SIMSP) or ‘Beautiful Smile for All’ programme is introduced. In this programme, a triad of dental hygienist-teacher-parent works together to improve children’s oral hygiene levels compared with the existing POHP that involves dental hygienists only. The aim of this study is to compare the effect of the SIMSP versus the existing POHP on oral hygiene levels of 5–6-year-old children in the Kampar district, Perak state, Malaysia. Methods This study is a pragmatic, cluster-randomised, parallel-group, matched pair, controlled trial with blinded outcome assessment. Randomisation is performed using a computer-generated table with a 1:1 allocation comparing the SIMSP and the POHP involving 28 preschools in the Kampar district, Perak, Malaysia. The intervention consists of preschool visits by a group of dental therapists, in-class oral health lessons and daily toothbrushing conducted by class teacher, child home toothbrushing supervised by parents, and infographic oral health messages to parents. The control consists of the existing POHP that involves preschool visits by a group of dental therapists only. The trial lasts for 6 months. Primary outcome variable is the mean plaque score change after 6 months. To determine the feasibility of the SIMSP, a process evaluation will be conducted using the perspectives of dental therapists, teachers, and parents on the appropriateness, effectiveness, facilitators, and barriers to the SIMSP implementation as well as an audit trail to assess the trial intervention. Discussion Cluster randomisation may lead to a random effect and cluster selection bias. These factors will be accounted for when analysing the data and interpreting the outcomes. The effectiveness of the SIMSP will be evaluated by comparing the results with those of the POHP. Trial registration ClinicalTrials.gov NCT04339647 . Registered on 5 April 2020 – Retrospectively registered.